The Development, Fine Specificity, and Importance of High-Avidity Antibodies to VAR2CSA in Pregnant Cameroonian Women Living in Yaoundé, an Urban City - Vanda, Koko; Bobbili, Naveen; Matsunaga, Masako; Chen, John J.; Salanti, Ali; Leke, Rose F. G.; Taylor, Diane Wallace (Frontiers in Immunology, 2021)
Pregnant women infected with Plasmodium falciparum often produce antibodies (Abs) to VAR2CSA, a ligand that binds to placental chondroitin sulfate A causing placental malaria (PM). Antibodies to VAR2CSA are associated with improved pregnancy outcomes. Antibody avidity is a surrogate marker for the extent of maturation of the humoral immune response. Little is known about high avidity Abs to VAR2CSA for women living in urban African cities. Therefore, this study sought to determine: i) if high avidity Abs to full-length VAR2CSA (FV2) increase with gravidity in women in Yaoundé, Cameroon exposed to ~ 0.3-1.1 infectious mosquito bites per month, ii) if high avidity Abs to FV2 are directed against a specific region of VAR2CSA, and iii) if having high avidity Abs to FV2 improve pregnancy outcomes. Plasma samples collected at delivery from 695 women who had Abs to FV2 were evaluated. Ab levels and the Avidity Index (AI), defined as the percent Abs remaining bound to FV2 after incubation with 3M NH4SCN, were determined. Similar Ab levels to FV2 were present in women of all gravidities (G1 through 6+; p=0.80), except significantly lower levels were detected in PM−negative (PM−) primigravidae (p <0.001). Median Ab avidities increased between gravidity 1 and 2 (p<0.001) and remained stable thereafter (G3-G6+: p=0.51). These results suggest that B cell clonal expansion began during the first pregnancy, with clonal selection primarily occurring during the second. However, the majority of women (84%) had AI <35, a level of high avidity Abs previously reported to be associated with improved pregnancy outcomes. When plasma from 107 Cameroonian women was tested against 8 different regions of FV2, high avidity Abs were predominately restricted to DBL5 with median AI of 50 compared to AI <25 for the other domains. The only significance influence of high avidity Abs on pregnancy outcome was that babies born to mothers with AI above the median were 104 g heavier than babies born to women with AI below the median (p=0.045). These results suggest that a vaccine that boosts maturation of the immune response to VAR2CSA may be beneficial for women residing in urban areas.